1979
DOI: 10.1111/j.1475-4754.1979.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

British Middle and Late Bronze Age Metalwork: Some Reanalyses

Abstract: IntroductionA study of major importance for our understanding of the composition of bronze artefacts of the Middle and Late Bronze Ages in Britain is the group of 438 analyses carried out by optical emission spectrometry by Brown and Blin-Stoyle (1959). Their description of the project and its conclusions were presented in that paper, and in a subsequent paper by Blin-Stoyle (1 959) the full analytical results for nine elements were published together with a comprehensive description of the emission spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The opportunity is also taken to publish a number of relevant analyses carried out in the Research Laboratory for Archaeology and History of Art in the University of Oxford in the early 1960's. It has since been suggested that some analyses made earlier in that laboratory (Brown and Blin-Stoyle 1959) used, at least in part, a wrong method for the determination of lead (Hughes 1979). However, re-analyses of some of the same material from the Selborne hoard for this project shows that there are several difficulties in accepting the Hughes analyses and the present analyses match those of Brown and Blin-Stoyle rather better.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The opportunity is also taken to publish a number of relevant analyses carried out in the Research Laboratory for Archaeology and History of Art in the University of Oxford in the early 1960's. It has since been suggested that some analyses made earlier in that laboratory (Brown and Blin-Stoyle 1959) used, at least in part, a wrong method for the determination of lead (Hughes 1979). However, re-analyses of some of the same material from the Selborne hoard for this project shows that there are several difficulties in accepting the Hughes analyses and the present analyses match those of Brown and Blin-Stoyle rather better.…”
Section: Discussionmentioning
confidence: 54%
“…This encourages the belief that it was in the Guilsfield area that lead entered the Wilburton distribution system, accumulating in thoseobjects where high lead contents were an advantage and being kept out of those where it was not desired. This pattern may have changed in the Ewart Park period with more lead sources being used and lead appearing in hoards (Lawson 1979). In the Wilburton period lead entered the system in finished objects and, at the end, in plate scrap.…”
Section: Leadmentioning
confidence: 99%
“…This alloy is broadly similar to that used in the Late Bronze Age (Brown & Blin-Stoyle 1959;Hughes 1979;Northover 1982a) while objects from the Iron Age proper (see below) only rarely contain appreciable amounts of lead. This alloy is broadly similar to that used in the Late Bronze Age (Brown & Blin-Stoyle 1959;Hughes 1979;Northover 1982a) while objects from the Iron Age proper (see below) only rarely contain appreciable amounts of lead.…”
Section: The Origins Of Iron Age Copper Metallurgymentioning
confidence: 72%
“…Because NAA is insensitive to lead, the Heidelberg lead analyses were conducted using isotope dilution mass spectrometry. As seen by Hughes (1979), there was a larger disagreement in lead concentration results between the earlier and later analyses. Although the overall impression from this comparison is good, we should note that agreement to within a factor of three is not a very high level of consistency.…”
Section: Data Inter-comparisonsmentioning
confidence: 77%
“…As well as these 'round robins', where several laboratories are invited to analyse the same materials, a number of targeted data inter-comparisons have been carried out, with the specific objective of assessing whether data produced by one method can be directly compared with those produced by another. For example, Hughes (1979) reanalysed using AAS some Middle and Late Bronze Age objects previously measured by OES, reported in Brown and Blin-Stoyle (1959), and found comparability for the elements Sb, Ag, Ni, Bi, Fe, As. However, the disagreement in the concentration of lead by these two techniques was shown to be large.…”
Section: Data Inter-comparisonsmentioning
confidence: 99%